Valoración económica y financiera de la sustitución de cultivos de cacao nacional por un tipo de clon de cacao denominado ccn-51. caso finca San Miguel - González C, Karen (2009)
In Los Rios, an Ecuadorian province, we find the “San Miguel” Farm, property of Josias Ruiz’s parents, coauthor of this article, in which we expose an offer to improve the actual production and incomes of the farm. Therefore, we evaluate the procedures used in the farm during the last years for the cultivation of its actual production lines National Cocoa and Corn comparing them with those recommended for professionals of the Universidad Tecnica Estatal de Quevedo (UTEQ) whom also helped us to collect important information for the investigation and evaluation of costs for a possible choice to replace the grows of National Cocoa, the Cocoa’s clone CCN-51, well known for its good flavor, very close to National Cocoa’s one, and its capacity to produce incomes even after two years from its planting. With all this information, we did a cash flow for everyone of the three options considering a five years temporal horizon. Some assumptions and even an ecometric model for prices were made. Finally, probability of having negative results is found for each case and after a selection of the two more profitable options we determine an optimal combination of the two selected plants using a maximization problem.